Adubação de mudas de baru (Dipteryx alata Vog.), em viveiro - PACHECO, Abílio Rodrigues (2008)
Producing seedlings of good quality is an important step in the process of planting forest species. Addition of lime and fertilizers contribute in obtaining good quality seedlings, however, information is limited on fertilization and nutrition of native species of savannah. The objective of this study was to evaluate growth response of baru seedlings (Dipteryx alata Vog.) to organic and mineral fertilizers. Seedlings were produced in plastic bags with a diameter of 20 cm x 30 cm and capacity of four liters of substrate. Clay Dark Red Latosol collected from subsoil (20 cm depth) from Federal District of Planaltina, DF was used. The first experiment was conducted in complete randomized blocks, with eleven treatments in a factorial arrangement (4X2), with three replications (composed of seedlings coming from different matrix) and plots consisted of three seedlings. The treatments tested were E0+D0, E10+D0, E20+D0, E30+D0, E0+D1, E0+D2, E0+ALL, E10+D1, E10+D2, E10+ALL and E20+D1, where: E0, E10, E20 and E30 are doses of cattle manure varied from 0 to 30% in relation to final volume of mixed subsoil; D1 and D2 are traditional rates of chemical fertilizers, and D2 is double of D1 and D1 equivalent to dolomitic lime incorporated in the subsoil (0,5 g L-1) + P (150 mg L-1) + K (200 mg L-1) + Zn (5 mg L-1) + Cu (5 mg L-1) + Mn (5 mg L-1) + B (1 mg L-1) + Mo (0,5 mg L-1) + N (50 mg recipient-1 month-1, diluted in water); P and K were applied in the form of triple superphosphate and potassium chloride, respectively, Zn, Cu and Mn in the form of sulfates, B and Mo in the forms of borax and sodium molibidate, respectively.; ALL is symbol of slow release fertilizer in six months (2.4 g recipient-1 after emergence of seedlings and five months of age), contain N (15%), P2O5 (10%), K2O (10%), Ca (3,5), Mg (1,5%), S (3%), B (0,02%), Cu (0,05%), Fe (0,5%), Mn (0,1%), Zn (0,05%) and Mo (0,004%). In others experiments (1, 2, 3, and 4) baru seedlings were submitted to four rates of dolomitic lime (0.0, 0.5, 1.0 and 2.0 g L-1 of substrate), P (0, 150, 300 and 600 mg L-1), K (0,100, 200 and 400 mg L-1) and N (0, 50, 100 and 200 mg seedling-1 month-1), in combination with two rates of cattle manure (10% and 20% in relation to final volume of mixture with subsoil). These experiments were conducted in complete randomized blocks in a factorial arrangement (4x2), with three replications (composed of seedlings coming from different matrix) and plots consisted of three seedlings. Source of N was urea (45% N), P triple superphosphate (45% P2O5), and K potassium chloride (60% K2O), respectively. After eight month of seedlings age following observations were made: Stem diameter of 5 cm height, plant height, top dry matter, soil and leaves chemical analysis for each treatment combination. In the first experiment, baru seedlings presented positive response to addition of traditional chemical fertilizers (rates D1 and D2) and slow release (ALL). Organic manure improved growth of seedlings with the addition of 20% and 30% cattle manure, however there was no difference between two rates. All treatments tested permitted production of seedlings of good quality for commercial sale and planting in the field, except of control treatment without fertilization (E0%+D0) and which received only 10% cattle manure with addition of subsoil (E10%+D0). Organic manure (20% cattle manure) and mineral fertilizers (D1, D2 and ALL) increased fertility of the substrate and leaf concentrations of N, P, K, S and Zn. In the experiments 1 and 4, seedlings presented positive growth to cattle manure incorporated in the subsoil, rate 20% better than rate 10%. Incorporation of cattle manure in the subsoil in the dose of 20%, supplied adequate fertilization in the substrate and foliar nutrition for growth and mineral nutrition of baru seedlings. In the presence of cattle manure incorporated in the subsoil in the 10 and 20% rates, seedling growth response was negative with the addition of potassium and there was no response with the addition of lime and phosphorus. Nitrogen topdressing monthly gave positive response to growth and height, stem diameter, top dry weight, when applied after incorporation of cattle manure in the subsoil in the dose of 10%, but response was positive in relation to height with rate of 20% cattle manure.